PENAMBAHAN LATEK ALAM PADA CAMPURAN LASTON BONGKARAN SEBAGAI POLIMER UNTUK PEREMAJAAN LAPISAN AC – WC - Sulaiman AR; Gusrizal Gusrizal; Bustamin Bustamin (Portal: Jurnal Teknik Sipil, 2022)
The durability of the Surface Course layer of road pavement construction is influenced by the mix between aggregate and asphalt according to each portion and the implementation system in the field. The material used must comply with predetermined specifications so that the construction will reach the design life if there is no overload during traffic service. In order to preserve the environment on the roadway overlays, construction is carried out on-site recycling or dismantling of the old coating elsewhere. Placement of demolition is also often a problem or pollution of the surrounding environment into waste. Avoiding this can be utilized by recycling and redesigning the demolition mixture by adding aggregate and asphalt content, or by adding other additives that can improve the AC-WC asphalt concrete mix. The author utilizes the results of the surface layer demolition material on KM 295-300 of the eastern causeway of Aceh Province by adding natural latex as a polymer material, specifically for the AC - WC surface layer because the layer is not structural. The research was started by extracting the demolition of the old asphalt layer so that the available bitumen content and aggregate granules were obtained. The research method is guided by applicable standards, grading using Bian Marga 2018 specifications and stability testing and others using the Marshall method. The extraction results obtained an asphalt content of 1.42%, while the optimum asphalt content was 6.2%, the marshall meter test showed that the addition of latex could increase the stability values, VMA, density, VFB, and MQ, while VIM was above 5% and flow was above 4 %, the optimum stability value at the addition of 15 % latex. Perfection needs further study by looking for other materials that can improve the value of flow and VIM in the mixture.